Molecular diagnosis of bovine genital campylobacteriosis using high-resolution melting analysis - Silva, Marta Filipa; Kienesberger, Sabine; Pereira, Gonçalo; Mateus, Luísa; Lopes-da-Costa, Luís; Silva, Elisabete (Frontiers in Microbiology, 2022)
Bovine Genital Campylobacteriosis (BGC) is a worldwide spread venereal disease of cattle caused by Campylobacter fetus subsp. venerealis (Cfv). Although several real-time PCR assays were developed for Cfv identification, most target mobile genetic elements, which may lead to false-positive diagnosis. In this study, a real-time PCR assay coupled with High-Resolution Melting analysis (HRM) was developed for the identification of Campylobacter fetus subspecies and application in BGC diagnosis. Two HRM assays targeting different single nucleotide polymorphisms were validated using 51 C. fetus strains, including 36 Cfv and 15 C. fetus subsp. fetus (Cff). The specificity was assessed in 50 preputial samples previously tested as negative for C. fetus and in 24 strains from other Campylobacter species. The analytical sensitivity was determined with ten-fold dilutions of Cfv genome copies and in preputial samples spiked with Cfv cells. Both HRM assays accurately identified the 51 C. fetus strains, showing 100% concordance with the previous identification. C. fetus subspecies identification by HRM showed concordant results with the glycine test in 98.0% of the isolates. No amplification was obtained in C. fetus negative preputial samples as well as in strains from other Campylobacter species. The assays were able to detect 102 genome copies of Cfv, while for preputial washing samples the limit of detection was 103 CFU/mL. These novel HRM assays represent a highly specific and sensitive tool for the identification of C. fetus subspecies and show potential for direct use in bull preputial samples for BGC diagnosis.